Dinamika Pembelian Impulsif Pada Toko Ritel Kesehatan Dan Kecantikan. Apakah Dipengaruhi Oleh Kualitas Layanan, Promosi Penjualan Atau Atmosfer Toko? - Rizna Ayuningsih; La Diadhan Hukama (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2025)
This study aims to determine and analyze Impulse buying of health, beauty and personal care products for consumers of health and beauty retail stores. This research uses an associative quantitative approach. Data collection in this study was carried out by distributing questionnaires online and offline to consumers who have made impulse purchases of health, beauty and personal care products at beauty retail stores. The questionnaire was processed using Microsoft MS analysis tools. Excel and SPSS. A total of 105 respondents were involved in this study. The results of this study found that service quality has a positive and significant effect on impulse buying, sales promotion has a positive and significant effect on impulse buying and store atmosphere has a positive and significant effect on impulse buying.